Knowledge about Child Growth and Development among Mothers and Community: A Qualitative Study in Wonosobo - Khairunnisa, Marizka; Yunitawati, Diah; Ashar, Hadi; Supadmi, Sri; Martiyana, Cati (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Optimal growth and development will produce qualified human resources. Achieving optimal growth and development requires support from various sectors, including parents, the community, and the government. This study aimed to determine the knowledge and awareness of mothers and the community regarding child growth and development in Wonosobo Regency, Central Java.Method: This qualitative study was conducted in Wonosobo, Central Java, in 2019. Data were collected using FGD with mothers of under-two children and cadres (two groups) and interviews with health workers and related stakeholders (10 informants). The data collected was then analyzed using thematic analysis.Result: The results showed that several themes related to child growth and development were identified, namely knowledge about child growth, development, stunting, and children’s growth and development problems (signs, causes, and prevention). Mothers and the community have the proper knowledge about child growth and development. However, there is still a low awareness of when a child needs special attention due to growth and development problems in mothers’ groups. Within the mothers’ group, the knowledge of growth and development mostly comes from their prior experience. Meanwhile, most of the community’s knowledge about child growth and development has been in line with health indicators. Bringing existing programs closer to the mothers could be an effort to increase knowledge and awareness about child growth and development.